Transfiguración y transformación: fin y medio de la cultura hesicasta - Пануева, Екатерина (Eslavística Complutense, 2005)
The article deals with the controversial secondary literature on the interdependence of various cultural and theological phenomena in fourteenth-century Bulgaria. The scholarly debate has resulted from the putative presence of contradictory characteristics noted for either different or identical works of the period, such as: tradition versus reformation, mysticism versus realistic tendencies etc. The overview at the end gives a possible explanation of the discrepancies noted: features mutually incompatible from the point of view of a present-day observer integrate with each other in fourteenth -century culture; there they do not contradict each other, but rather pursue the same aim through different means.
Keywords: Hesychasm; Orthodox; Fouríeenth-centuty culture; Bulgaria